Vpliv 8-tedenskega programa športne vadbe na gibalne sposobnosti in telesne značilnosti žensk s prekomerno telesno maso ter posebnosti testiranja - Glavač, Ana (Šport (Ljubljana), 2019)
The purpose of the study was to determine how 8-week training program for overweight women affects their motor capabilities and physical characteristics and determine specificites of testing this population. The survey included 13 female overweight individuals (average body mass was 110,2 kg) with a BMI higher than 30 kg/m2, aged 31,9 +- 4. The motor capability assessment consisted of 9 tests, which were used to measure flexibility, strength endurance and endurance. We used Tanita (model BC 601, Ilinois, USA) to measure body characteristics (body weight, percentage of body fat and muscle mass). In addition to the abovementioned parameters we measured abdominal, waistline and thigh circumferences as well. We used the program IBM SPSS 21 to statistically analyze the data. We compared the differences between the initial and final states with the T-test for dependent samples. All the analyses were carried out at the characteristic level p <_ 0.05. The study showed us that 8-week training program statistically significant affects on motor capabilities and physical characteristics on women with excessive body weight.
Keywords: debelost; exercise program; fitenss tests; fitnes testi; obesity; overweight people; prekomerna telesna teža; sport; šport; športna vadba